Correlates of Neuropsychological Impairment in Older Adult Pain Clinic Patients - Karp, Jordan F. (2006)
OBJECTIVE: Persistent pain and cognitive impairment are common in older adults. Memory and mental flexibility are cognitive domains which may be vulnerable in the aging brain. We were interested in examining the effects of persistent pain and opioid use on cognition in community dwelling, non-demented older adults. SETTING: Older Adult Pain Management Program. DESIGN: 57 new patients (mean age 76.1) were recruited to describe 1) rates of persistent pain conditions and pain intensity, 2) cognition (memory and mental flexibility), 3) rates and severity of depression, and 4) sleep quality. All patients had non-malignant pain for at least 3 months. Pain intensity was measured with the McGill Pain Questionnaire. Diagnosis of depression was via the Patient Health Questionnaire and depression severity assessed with the Hamilton Rating Scale for Depression. Cognition was assessed with: 1) Mini Mental State Examination, 2) number-letter-switching and motor speed trail-making subtests, 3) Digit Symbol Subtest of the WAIS-R, and 4) free and paired recall of the WAIS-R. To determine which variables predicted poorer outcomes on mental flexibility tests, these variables were entered into a multiple regression. RESULTS: Pain severity was associated with impaired number-letter switching (r = −0.42, p = 0.002). Multiple regression showed pain severity was associated with impaired mental flexibility (parameter estimate = −0.29 (t = −2.00), p = 0.05). Patients taking opioids had worse memory (t = 2.17, df = 39, p = 0.04). CONCLUSIONS: In community-dwelling older adults, pain severity is associated with impaired mental flexibility. In addition, opioids may increase memory problems.